2007
DOI: 10.1007/s11095-007-9428-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Plasma Cholesterol and Triglyceride Concentrations and Eritoran (E5564) Micelle Size on its Plasma Pharmacokinetics and Ex Vivo Activity Following Single Intravenous Bolus Dose Into Healthy Female Rabbits

Abstract: These findings suggest that plasma pharmacokinetics and activity of eritoran maybe influenced by eritoran micelle size and plasma TC and TG concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…bolus required to maintain blood levels at 50-100 ng/mL over 2 days and to inhibit the increase in TNFα levels in mice treated with LPS. [19] …”
Section: Tlr4mentioning
confidence: 99%
“…bolus required to maintain blood levels at 50-100 ng/mL over 2 days and to inhibit the increase in TNFα levels in mice treated with LPS. [19] …”
Section: Tlr4mentioning
confidence: 99%
“…These metabolites are eliminated slowly from the body mainly through feces32. Eritoran formulated in small micelles (8 nm) resulted in increased AUC 0–72h and drug concentration at 5 min, and decreased clearance than large micelles (27 nm) in rabbits33.…”
Section: Eritoran Tetrasodiummentioning
confidence: 99%
“…In such case, scientists have also tried to find a single protein that could achieve a dramatic therapeutic outcome for these various diseases and TLR4 has been considered one of the best candidates [12,38]. New drugs developed to inhibit TLR4 activity are already in various phases of preclinical and clinical trials for treating acute and chronic inflammation, colitis, sepsis, chronic pain, and addiction withdrawal [12,[17][18][19][20][21]. In animal studies, TLR4 activity inhibition has also been demonstrated to reduce the levels of atherosclerosis and myocardial inflammation [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…TLR4/MD2 signaling further contributes to the secretion of proinflammatory cytokines and chemokines and hence leads to the development of immune and inflammatory diseases. Therefore, TLR4 has become a target for drug design and development, and some such drugs for the treatment of lung inflammation, sepsis, and rheumatoid arthritis have already entered preclinical and clinical trials [12,[17][18][19][20][21]. Recently, TLR4 has been associated with other chronic inflammatory diseases, such as diabetes and atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%